Structural basis for inhibition of cyclin-dependent kinase 9 by flavopiridol - Filgueira de Azevedo Jr., Walter [UNESP]; Canduri, Fernanda [UNESP]; Freitas da Silveira, Nelson José [UNESP] (Elsevier, 2002)
Flavopiridol has been shown to potently inhibit CDK1 and 2 (cyclin-dependent kinases 1 and 2) and most recently it has been found that it also inhibits CDK9. The complex CDK9-cyclin T1 controls the elongation phase of transcription by RNA polymerase II. The present work describes a molecular model for the binary complex CDK9-flavopiridol. This structural model indicates that the inhibitor strongly binds to the ATP-binding pocket of CDK9 and the structural comparison of the complex CDK2-flavopiridol correlates the structural differences with differences in inhibition of these CDKs by flavopiridol. This structure opens the possibility of testing new inhibitor families, in addition to new substituents for the already known leading structures such as flavones and adenine derivatives. © 2002 Elsevier Science (USA). All rights reserved.
Keywords: Bioinformatics; CDK; Drug design; Flavopiridol; Structure; 2,6 diamino 4 cyclohexylmethoxy 5 nitrosopyrimidine; 6 n (3,3 dimethylallyl)adenine; 6 o cyclohexylmethylguanine; adenine derivative; adenosine triphosphate; cyclin dependent kinase; cyclin dependent kinase 2; cyclin dependent kinase 9; cyclin T1; dechloroflavopiridol; enzyme inhibitor; flavone derivative; flavopiridol; hymenialdisine; indirubin; olomoucine; pkfo 49 38; purvalanol B; roscovitine; staurosporine; u 55; unclassified drug; correlation analysis; drug potency; drug protein binding; drug structure; enzyme inhibition; IC 50; molecular model; priority journal; structure activity relation; structure analysis; Amino Acid Sequence; Cyclin-Dependent Kinase 9; Cyclin-Dependent Kinases; Enzyme Inhibitors; Flavonoids; Models, Molecular; Molecular Sequence Data; Piperidines; Protein Conformation; Sequence Alignment; Sequence Homology, Amino Acid